2017
DOI: 10.1002/gps.4661
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between help‐seeking for early detection of Alzheimer's disease and illness representations of this disease among the lay public?

Abstract: Our findings stress the need to increase the lay public's knowledge about available treatment options and their efficacy, even in the advances stages of the disease when the consequences of the disease are much more severe. AD awareness programs should also pay attention to the potential fear which may exist in the case of HS for early detection of AD. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Among these publications, four outcome variables were examined: help-seeking, professional burnout, sense of coherence, and willingness to discuss concerns about cognitive changes. Findings showed that students and the lay public were more likely to indicate an intention to seek help if they perceived dementia as having severe symptoms and consequences, such as permanent damage, with higher perceived coherence 33,35. Among older adults with subjective memory complaints, it was found that IRs including social comparison and causal attributions predicted help-seeking behavior 26.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Among these publications, four outcome variables were examined: help-seeking, professional burnout, sense of coherence, and willingness to discuss concerns about cognitive changes. Findings showed that students and the lay public were more likely to indicate an intention to seek help if they perceived dementia as having severe symptoms and consequences, such as permanent damage, with higher perceived coherence 33,35. Among older adults with subjective memory complaints, it was found that IRs including social comparison and causal attributions predicted help-seeking behavior 26.…”
Section: Resultsmentioning
confidence: 97%
“…It should be noted that research in the area of dementia and IRs is mostly descriptive, and only few studies have examined correlates of IRs. Three studies found an association between IRs and help-seeking 26,33,35. This is a significant finding for two reasons.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Three per cent of participants in Luck et al [ 39 ] agreed that ‘scientific research’ could reduce the risk for dementia but did not specify to what research this referred ( n = 1002). Finally, Shinan-Altman et al [ 48 ] did not report raw scores and could not be pooled, but reported below average endorsement on a scale of one (strongly disagree) to five (strongly agree) that AD is attributable to risk factors (M = 2.47), psychological factors (M = 2.05), and immunity (M = 1.83).…”
Section: Resultsmentioning
confidence: 99%
“…Early awareness of a disease, familiarity with likely symptoms, readiness to seek early diagnosis could serve physicians and individuals in early treatment, and at the same time could ease the burden on society of late-stage treatment [46]. …”
Section: Educating the Publicmentioning
confidence: 99%